Exploring School Ergonomics: Backpack Use, Writing Posture, and Musculoskeletal Health in Children with Spinal Deformity (Global Journal of Medical Research, 2023)
Purpose School ergonomics affects musculoskeletal system of children as many loads may lead to biomechanical impairments for a growing body The purpose of this study was to determine the weight of school backpack backpack positioning on back handwriting position and correlate them with number of other postural deformities of children who had spinal deformity Methods This is a cross-sectional study which includes 108children who had at least one spinal deformity School backpack weight backpack positioning handwriting posture and their correlations with postural deformities were analyzed Body weight backpack weight and backpack position were recorded Writing position was assessed by Rapid Upper Limb Assessment RULA Posture analysis was conducted with observation to record other deformities except spinal deformities and total number of these deformities was recorded
Keywords: primary school; backpack; handwriting; posture